Contemporary sequential narratology with focus on reading dynamics (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2016)
Review of Baroni, Raphaël and Françoise Revaz, eds. Narrative Sequence in Contemporary Narratology. Columbus: Ohio State University Press, 2016.